The Uniqueness of commercial banks - Guttentag , Jack M.; Lindsay, Robert (Chicago Journal of Political Economy, 1968)
Today's banking sytems may not be in as good a shape as is generally assumed. While most banks' profits continue to come from lending, many have been exposed to lesser borrowers, and have entered into other businesses such as asset management. This work considers changes in commercial banking.
aia 15/03/2019
Loans
Keywords: Banks and Banking